Sequence of a Drosophila segmentation gene: protein structure homology with DNA-binding proteins. - Laughon, A.; Scott, M.P. (Nature, 1984)
Mutations in the fushi tarazu (ftz) locus of Drosophila result in embryos with half the usual number of body segments. The sequences of the wild-type gene, a temperature-sensitive allele and a dominant mutant allele are presented. A portion of the conserved protein domain present in ftz and several homoeotic genes resembles the DNA-binding region of prokaryotic DNA-binding proteins, and is also similar to products of the yeast mating-type locus.